2020
DOI: 10.1177/1071100720963077
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Patient-Reported Outcome Measures Relationship With Postoperative Outcomes in Flexible Adult-Acquired Flatfoot Deformity

Abstract: Background: Previous studies have demonstrated that procedure-specific thresholds using preoperative patient-reported outcome scores may be used to predict postoperative outcomes. The primary purpose of this study was to determine if preoperative Patient-Reported Outcomes Measurement Information System (PROMIS) thresholds could be used to predict which patients would clinically improve at 2 years postoperatively following reconstruction of their flexible adult-acquired flatfoot deformity (AAFD). Methods: PROMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…Because the MCIDs from the bootstrapped analysis were all within 0.1 of the estimates from the original sample, the MCIDs from the original sample were used in the analysis because this method has been used in previous studies. 5,18,19,25 Logistic regression models controlling for age, gender, and body mass index (BMI) were then used to evaluate the predictive value of preoperative PROMIS scores in determining meaningful improvement after surgery based on the MCID. The area under the curve (AUC) was calculated in order to ascertain the ability of a PROMIS scale to differentiate between those patients who had meaningful improvement and met the MCID postoperatively and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Because the MCIDs from the bootstrapped analysis were all within 0.1 of the estimates from the original sample, the MCIDs from the original sample were used in the analysis because this method has been used in previous studies. 5,18,19,25 Logistic regression models controlling for age, gender, and body mass index (BMI) were then used to evaluate the predictive value of preoperative PROMIS scores in determining meaningful improvement after surgery based on the MCID. The area under the curve (AUC) was calculated in order to ascertain the ability of a PROMIS scale to differentiate between those patients who had meaningful improvement and met the MCID postoperatively and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…The improvements in Physical Function and Pain Interference were substantially greater than the reported minimal clinically important differences for PCFD of 3.2 points and 3.7 points on the PROMIS PF and PI subscales, respectively. 4…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies using similar methodology have suggested that preoperative PROMIS scores are associated with out comes in surgical foot and ankle patients in general, and further research has been done to identify diseasespecific thresholds to determine if preoperative PROMIS scores have clinical utility in associating with outcomes after spe cific procedures such as bunionectomy, flatfoot reconstruc tion, and TAR. 1,3,4,8,13 Ho et al 8 found that preoperative PROMIS physical function (AUC = 0.83), pain interfer ence (AUC = 0.73), and depression (AUC = 0.74) scores were associated with postoperative outcomes in a sample of 61 surgical foot and ankle patients. Patients in their cohort that had a physical function score <29.7 had an 83% prob ability of achieving the MCID, and patients with a score >42 had a 94% probability of failing to achieve the MCID.…”
Section: Discussionmentioning
confidence: 99%
“…For pathologies such as progressive collapsing foot deformity, ankle arthritis, and hallux valgus, preoperative PROMIS scores may be a useful adjunct to clinical examination to give clinicians and patients an idea of how much they can improve after surgery. 3,4,13 However, for hallux rigidus, preoperative outcome scores cannot be used to give patients a prognosis on how much they will improve after a cheilectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation